Computational modelling of mobile bearing TKA anterior–posterior dislocation. Issue 5 (3rd April 2016) - Müller, J.H.; Zakaria, T.; van der Merwe, W.; D'Angelo, F.
Abstract : Anterior–posterior stability in an unconstrained mobile-bearing total knee arthroplasty (TKA) and one with rotational constraints is compared in a computational model based on an ASTM test. Both TKA designs dislocate at loads greater than reported maximum in vivo forces. The posterior drawer forces (mean: 3027 N vs. 1817 N) needed to induce subluxation increase with a greater anterior jump distance (12 mm vs. 7 mm; refers to the vertical height of the anterior or posterior border of the tibial insert's articulating surface). The posterior jump distance for both tested TKA differed by 1.5 mm and had minimal effect on the magnitude of the anterior drawer forces at dislocation in mid-flexion (unconstrained vs. constrained: 445 N vs. 412 N). The unconstrained insert dislocated by means of spin-out whereas in the constrained TKA the femur dislocated from the bearing during posterior drawer and the bearing from the baseplate during anterior drawer. MCL function is an important consideration during ligament balancing since a ± 10% variation in MCL tension affects dislocation forces by ± 20%. The simulation platform provided the means to investigate TKA designs in terms of anterior–posterior stability as a function of knee flexion, collateral ligament function and mechanical morphology.